2017
DOI: 10.1016/j.molcel.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Guide RNA Processing and Seed-Dependent DNA Targeting by CRISPR-Cas12a

Abstract: The CRISPR-associated protein Cas12a (Cpf1), which has been repurposed for genome editing, possesses two distinct nuclease activities: endoribonuclease activity for processing its own guide RNAs and RNA-guided DNase activity for target DNA cleavage. To elucidate the molecular basis of both activities, we determined crystal structures of Francisella novicida Cas12a bound to guide RNA and in complex with an R-loop formed by a non-cleavable guide RNA precursor and a full-length target DNA. Corroborated by biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

51
659
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(713 citation statements)
references
References 61 publications
51
659
1
2
Order By: Relevance
“…Thus, these observations suggested that the Cpf1 Nuc domain plays a role in guiding the target strand into the RuvC active site, rather than catalyzing the cleavage of the target strand. Supporting this notion, a recent study indicated that Francisella novicida Cpf1 cleaves the target and non-target DNA strands, using the same RuvC domain active site (Swarts et al, 2017). …”
Section: Resultsmentioning
confidence: 96%
“…Thus, these observations suggested that the Cpf1 Nuc domain plays a role in guiding the target strand into the RuvC active site, rather than catalyzing the cleavage of the target strand. Supporting this notion, a recent study indicated that Francisella novicida Cpf1 cleaves the target and non-target DNA strands, using the same RuvC domain active site (Swarts et al, 2017). …”
Section: Resultsmentioning
confidence: 96%
“…In the first stage, adaptation of a complex of Cas1, Cas2, and in some cases additional Cas proteins mediates excision of fragments from the target DNA (these fragments are known as protospacers), followed by their insertion into the CRISPR array, typically at the leader end of the array (3,12). In the second stage, the CRISPR array is transcribed, and the primary transcript, the pre-CRISPR RNA, is processed into mature CRISPR RNAs (crRNAs) either by a distinct complex of Cas proteins (in type I and type III class 1 CRISPR-Cas systems), by the effector protein (in type VA and type VI systems of class 2), or by the bacterial RNase III with aid from the trans-acting CRISPR (tracr) RNA (in type II and type V-B systems of class 2) (13)(14)(15)(16)(17)(18). The mature crRNA consists of a unique spacer of 25 to 65 bp in length (depending on the CRISPR-Cas type and subtype) flanked by portions of the adjacent repeats.…”
mentioning
confidence: 99%
“…Based on the similarity of domain organization, effectors associated with these five sub-types have been classified as variants of the Cas12 family. Only Cas12a (formerly Cpf1) and Cas12b (formerly C2c1) have been extensively characterized both structurally and functionally (Dong et al, 2016; Gao et al, 2016; Liu et al, 2017a; Shmakov et al, 2015; Stella et al, 2017; Swarts et al, 2017b; Wu et al, 2017; Yamano et al, 2016; Yang et al, 2016; Zetsche et al, 2015). Two additional Type V effectors, Cas12d (formerly CasY) and the compact 980 amino acid Cas12e (formerly CasX), have demonstrated RNA-dependent DNA interference activity in in vivo studies (Burstein et al, 2017), while activity of Cas12c (formerly C2c3) has not been established (Shmakov et al, 2015).…”
Section: Type V Crispr-cas Systemsmentioning
confidence: 99%
“…Formation of the RNA:DNA heteroduplex is stabilized through backbone interactions within the cleft formed between the REC and NUC lobes. Interestingly, although the Cas12a crRNA guide region is 24 nt, 4 nt longer than Cas12b, RNA:DNA heteroduplex formation is interrupted after 20 base pairs by the insertion of an aromatic sidechain, resulting in a duplex that is the same length as in Cas12b (Swarts et al, 2017b; Yamano et al, 2016) (Figure 1F–G, 3D, F). …”
Section: Type V Crispr-cas Systemsmentioning
confidence: 99%
See 1 more Smart Citation